(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2019)
This study aims at evaluating the quality of groundwater for drinking purposes in the city of Sorman, Libya, using Water Quality Index (WQI). The city is located to the northwest of Libya. The study is based on samples collected from twenty-nine wells in different locations of the city during summer period of 2017. The Groundwater samples were analyzed for pH,EC,TDS, and other major ions. For calculating WQI, eleven parameters have been considered. The suitability of groundwater in the study area for human consumption purpose was achieved by WQI according to the guideline values of World Health Organization (WHO 2011). for chemical parameters. The weights (Wi) of the parameters were assigned according to their influence on the human health. The results showed that the (WQI) values groundwater in the study area varied from good to unsuitable for human drinking purpose.